1986
DOI: 10.3109/00365528609003108
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Shorter Than 24-H pH Monitoring Periods in the Diagnosis of Gastro-Oesophageal Reflux

Abstract: We studied 20 patients with typical symptoms of gastro-oesophageal reflux, to determine whether the diagnostic accuracy of 24-h pH monitoring might be retained in a test using a shorter time. The duration and number of reflux episodes were used to calculate a frequency and duration score (FDS) for the 24-h period, the daytime period, the nighttime period, a 3-h postprandial period after eating a test meal (provocation test), and a 21-h period that excluded this 3-h postprandial period. The daytime FDS was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In most previous investigations of reflux patterns, oesophageal motor activity was evaluated by means of short term manometry carried out before pH monitoring and without knowledge of actual intra-oesophageal pH at the time of measurement.3'7 8 17 18 Frequent contractions during intervals of normal pH may contribute to frequent relaxation of the gastro-oesophageal sphincter. The high pressure activity during normal pH seen in the patient groups may therefore, to some extent, explain why they had frequent episodes of reflux as well as prolonged reflux.…”
Section: Resultsmentioning
confidence: 99%
“…In most previous investigations of reflux patterns, oesophageal motor activity was evaluated by means of short term manometry carried out before pH monitoring and without knowledge of actual intra-oesophageal pH at the time of measurement.3'7 8 17 18 Frequent contractions during intervals of normal pH may contribute to frequent relaxation of the gastro-oesophageal sphincter. The high pressure activity during normal pH seen in the patient groups may therefore, to some extent, explain why they had frequent episodes of reflux as well as prolonged reflux.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 3‐hour recording is likely to be better tolerated, compared to longer duration recording, even if ambulatory. In fact, the number of acidic reflux events as well as acid exposure for 3‐hour post‐prandial recording using standardized test meals, has been shown to correlate with results obtained at 24‐hour recording . However, shorter duration of recording increases intra‐individual variations …”
Section: Discussionmentioning
confidence: 99%
“…In fact, the number of acidic reflux events as well as acid exposure for 3-hour post-prandial recording using standardized test meals, has been shown to correlate with results obtained at 24-hour recording. [7][8][9] However, shorter duration of recording increases intra-individual variations. 6 In the present work, using 24-hour recording as a gold standard, we showed, that shorter duration of esophageal multichannel intraluminal impedance (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators, for example, have revealed that the development of esophagitis is related to increased supine reflux [5,24,[28][29][30] . Others have found evidence to support the opinion that daytime gastroesophageal reflux plays a more important role in the development of esophagitis [31][32][33][34] . Although there are different opinions as to the relationship between patterns of GER and esophagitis, it is generally recognised that a difference in patterns of GER is related to the development of esophagitis.…”
Section: Re Pr Phr Phrementioning
confidence: 95%